Amadurecimento de caqui 'fuyu' em função da exposição ao frio, atmosfera controlada e 1-MCP - Pinto, Josuel Alfredo Vilela (2009)
Aiming to understand the mechanism of ripening of the Fuyu persimmon and extend the storage period, experiments were preformed to evaluate the effect of the period of exposure to low temperature, controlled atmosphere and inhibitor the ethylene action in the beginning or in the end of storage period on the incidence of softening. In the first experiment following treatments were evaluated: [1] 3 days at -0.5°C; [2] 6 days at -0.5°C; [3] 9 days at -0.5°C; [4] 6 days at 10°C; [5] 9 days at 10°C; [6] 15 days at 10°C; [7] 9 days at 15°C and [8] 15 days at 15°C. In the second experiment treatments were obtained by combining the temperature (-0.5; 10; 12.5; 15 e 17.5°C) with and without application of 1-methylcyclopropene (1-MCP), before storage. The laboratory tests were performed after 1 and 2 months storage. In the third experiment at -0.5ºC were evaluated the treatments: [1] cold storage(CS), [2] application of 1ppm of 1-MCP and subsequent CS, [3] CS and subsequent application of 1-MCP, [4] controlled atmosphere (CA) with 1.0kPa O2 + 8.0kPa CO2, [5] application of 1-MCP and subsequent storage in CA, [6] CA storage and subsequent application of 1-MCP. The laboratory tests were performed after 2 months in fruits storage in CS and after 4 months in fruits storage in CA. According to the results of the experiments the period of 9 days at -0.5ºC does not provide sufficient cooling to stimulate the maturation process of persimmon, do not altering the production of ethylene, respiration and softening of the fruit when compared with 15ºC. The storage of Fuyu persimmon for one month at -0.5ºC is sufficient to stimulate the maturation process, with 100% fruit softened after 6 days at 20°C. Already, storage for two months at -0.5°C accelerates the maturation process and leaving 100% fruit soft after 4 days at 20°C. At the temperatures of 10, 12.5 and 15°C occurred softening of fruit during storage, showing that these temperatures for long periods, are also efficient in the unlock process of maturation. The softening is related with the ethylene action and probably with its receptor. The application of 1-MCP before or after storage block the maturation process even in fruit exposed at -0.5°C, not occurring softening after exposure at 20°C. Controlled atmosphere delayed the softening. CA condition with 1.0kPa O2 + 8.0kPa CO2 with application of 1-MCP was the most efficient treatment to control the maturation, but occurred high incidence of decay after 4 months storage of Fuyu persimmon.